The Impact Of Waiting Time And Service Satisfaction On Patient Loyalty At The Dental Clinic - Purwantiningsih, Meiyanti; Sikki, Nurhaeni; Malik, Rahadian (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2025)
This study aims to analyze the influence of waiting time and service satisfaction on outpatient loyalty at the Dental Clinic of the Sukalarang Community Health Center, Sukabumi Regency. A total of 100 respondents were selected using purposive sampling. Data were analyzed using the Partial Least Squares (PLS) approach to assess the impact of both variables individually and simultaneously on patient loyalty. The results show that, partially, service satisfaction has a significant effect on patient loyalty, while waiting time does not exhibit a statistically significant influence. However, when considered simultaneously, both variables contribute significantly to patient loyalty. These findings highlight the significant role of service quality in promoting patient loyalty, with efficient waiting time management serving as a crucial factor in shaping positive patient perceptions. The study implies that strategies to enhance patient loyalty in dental healthcare services should prioritize improving professional, responsive, and patient-centered care.